PERAN EDUKASI DAN LINGKUNGAN DALAM PENGEMBANGAN MINAT MAHASISWA BERWIRAUSAHA - Darmayanti, Elmira Febri; Rahayu, Sri Retnaning (Jurnal Manajemen Magister Darmajaya, 2018)
The purpose of this research aims to analyze and describe influence between variables that used in this research. The object of the study used 151 students of the Faculty of Economics and Business (FEB) UM Metro as random sampling. The data are collected using questionnaires and observation Data analysis in this study is included in quantitative and qualitative research. Research analysis uses Structural Equity Modeling (SEM). The collected data was processed with the Smart-PLS 3.0 program using a non-response bias test, data quality test, model test, hypothesis test, and variable descriptive analysis. The results showed that entrepreneurship educational and entrepreneurial interest has a significant and positive influence, environment and entrepreneurial interest has a significant and positive influence too. This shows that FEB UM Metro students have a high interest in entrepreneurship after gaining knowledge through entrepreneurship education.Keyword: Entrepreneurship, Educational, Environment, Entrepreneur Interest.